2022
DOI: 10.48550/arxiv.2205.11269
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamic Split Computing for Efficient Deep Edge Intelligence

Abstract: Deploying deep neural networks (DNNs) on IoT and mobile devices is a challenging task due to their limited computational resources. Thus, demanding tasks are often entirely offloaded to edge servers which can accelerate inference, however, it also causes communication cost and evokes privacy concerns. In addition, this approach leaves the computational capacity of end devices unused. Split computing is a paradigm where a DNN is split into two sections; the first section is executed on the end device, and the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…For instance, the downsampled images in NUD and compressed representation in TOIC can be transmitted instead of the original inputs. This would be a form of split computing (also known as collaborative intelligence) [166], [167], where the initial portion of computation is performed on a resource-constrained end-device, and the compact intermediate representation is then transmitted to a server where the rest of the computation is carried out. A study using this idea for high-resolution images captured by drones is reported in [168].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the downsampled images in NUD and compressed representation in TOIC can be transmitted instead of the original inputs. This would be a form of split computing (also known as collaborative intelligence) [166], [167], where the initial portion of computation is performed on a resource-constrained end-device, and the compact intermediate representation is then transmitted to a server where the rest of the computation is carried out. A study using this idea for high-resolution images captured by drones is reported in [168].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, solutions can be created to bring computational capacity closer to the edge of the network to avoid data transmission to the cloud for processing and alleviate critical problems related to latency [14], energy consumption [15], bandwidth and scalability [16]. Furthermore, the integration with artificial intelligence empowers machines with human-like intelligence and includes knowledge-based perception and decision-making capabilities [17]. Therefore, in this research we focus on evaluating algorithms based on neural networks adapted to an edge device in the context of a human activity recognition application [18].…”
Section: Introductionmentioning
confidence: 99%